How Do Customers React to Technology in the Hospitality and Tourism Industry? - Arici, Hasan Evrim; Saydam, Mehmet Bahri; Koseoglu, Mehmet Ali (SAGE Publications, 2023)
Growing scientific attention to technology has led to new guidelines for comprehending consumers’ experiences with the technology. Understanding the relationship between technology and consumers is crucial for advancing thought as well as practice in this subject. This study aims to look at the origins, significant subjects, scientific advances, and future advancements in customer reactions to technological research. To accomplish this aim, we ran analysis in R with the visualization tools VOSviewer and Biblioshiny in order to conduct a bibliometric study. Employing the Boolean strategy, journal articles were obtained from the Scopus database up to August 17, 2022. This research looked at customer reactions to technology literature from various angles, including citations, journals, keywords, and geographies. Then, bibliographic coupling, co-citation, and co-occurrence analysis were carried out. The analysis showed how customer reactions to technology literature have changed over the past 2 decades. This study provided insight into the role of technology adoption and COVID-19 in customer reactions to technology, and identified potential and constraints in this area.